2017
DOI: 10.1038/s41598-017-02991-8
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Reconstruction After Radical Prostatectomy: A Systematic Review and Meta-analysis of Different Surgical Techniques

Abstract: Radical prostatectomy (RP) is the gold standard for the treatment of localized PCa. A meta-analysis was conducted to evaluate the effect of different techniques of pelvic floor reconstruction on urinary continence. A comprehensive search was made for trials that evaluated the efficacy of pelvic floor reconstruction. Relevant databases included PubMed, Embase, Cochrane, Ovid, Web of Science databases and relevant trials from the references. Random-effects model was used to estimate risk ratios (RRs) statistics.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Grasso et al [42] reported a meta-analysis demonstrating that posterior reconstruction during RALP had a significant advantage on urinary continence in the first 30 days (relative risk, 1.60; 95% CI, 1.20-2.12; p < 0.0001); however, there was no significant advantage in terms of urinary incontinence after 90 and 180 days. Cui et al [43] demonstrated that anterior suspension (Patel's stitch) was also associated with short-term urinary continence, but not with long-term outcomes. Wu et al [44] performed a meta-analysis to evaluate the efficacy of total reconstruction (anterior plus posterior reconstruction) versus non-total reconstruction of the pelvic floor on the urinary continence rate after RP, with eight robotic and two laparoscopic RP series.…”
Section: Discussionmentioning
confidence: 99%
“…Grasso et al [42] reported a meta-analysis demonstrating that posterior reconstruction during RALP had a significant advantage on urinary continence in the first 30 days (relative risk, 1.60; 95% CI, 1.20-2.12; p < 0.0001); however, there was no significant advantage in terms of urinary incontinence after 90 and 180 days. Cui et al [43] demonstrated that anterior suspension (Patel's stitch) was also associated with short-term urinary continence, but not with long-term outcomes. Wu et al [44] performed a meta-analysis to evaluate the efficacy of total reconstruction (anterior plus posterior reconstruction) versus non-total reconstruction of the pelvic floor on the urinary continence rate after RP, with eight robotic and two laparoscopic RP series.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first description in 2006 ( 16 ), the technique gradually spread and has been successfully adapted to minimally invasive surgery. Its benefit on early urinary continence recovery after radical prostatectomy has been reported in a Cochrane review by Rosemberg et al ( 17 ) and another meta-analysis ( 18 ).…”
Section: Discussionmentioning
confidence: 79%
“…As this development can vary substantially from patient to patient, the fascia can have a multilayer configuration, fragmentation into short pieces, or be composed of a thick leaf (28). Reconstruction of the posterior musculofascial plate (initially described by Rocco et al "Rocco stitch") has been demonstrated to have a beneficial impact predominantly on short-term continence rates (30)(31)(32)(33). Whether some specific modifications in the reconstruction approach, such as a 3-layer/2-step approach (including peritoneum) instead of the initially 2-layer/2-step approach by Rocco et al will result in remarkable continence improvements has to be proven in the future (30,34).…”
Section: Posterior Prostatic Fascia/seminal Vesicles Fasciamentioning
confidence: 99%